Management of infantile hemangiomas: Recent advances - Xu, Wei; Zhao, Haiguang (Frontiers in Oncology, 2022)
Infantile hemangiomas are a benign vascular tumor that is commonly seen in children. A small number of cases can manifest as organ or system dysfunction, permanent scarring, or even disfigurement in clinic. The diagnosis is currently mainly based on clinical history, physical examination, and combining with auxiliary inspection sometimes. In the treatment of hemangioma, the functional damage caused by the lesion and the complications that may endanger the patient's life should be given priority. Which suggested that the early identification and referral to specialists are important factors to prevent related complications and obtain a better prognosis. During the past decades, researchers have explored different treatments according to the condition, including timolol, steroid hormones, sirolimus, propranolol, laser surgery, high intensity focused ultrasound, and surgical treatment. This article will be primarily on the recent advances in clinical diagnosis and the treatment of hemangioma, along with a literature review on the subject.